The Definitive Guide to SWT and JFace - Warner, Rob (Apress, 2013)
This book doesn't teach you Java. It also doesn't teach you how to use Eclipse, nor does it teach you how to build Eclipse plug-ins. You can find a number of other books that teach Java or Eclipse, many of them excellent and deserving of your time and study. This book ignores specific tools, however, and instead focuses on the SWT and JFace libraries to help you build independent desktop applications.